Illegality of Imposing Comprehensive Sanction on Iraq: Contradiction Policy of Security Council - Saleh, Mohammed Mahdi (European Scientific Journal, ESJ, 2016)
During the history of the United Nations, Security Council have imposed partial and comprehensive sanctions on some countries. In all these resolutions, humanitarian commodities including foodstuff and medicine were exempted except in Iraq where foodstuff and medicine were included in the sanction regime. This has resulted to large scale of humanitarian crises during the thirteen years of sanction. The aim of this paper is to examine whether or not the Security Council has authority to adopt such complete siege in preventing Iraq from importing humanitarian commodities. It also aims to ascertain whether or not the Security Council exceeded its authority illegally and punished the whole Iraqi people for political reasons.